Circularity potentials, influential factors, modeling approach and policy interventions of circular supply chain for electric vehicles - Karsi Widiawati; Bertha Maya Sopha; Benny Tjahjono; Naly Rakoto (Cleaner Engineering and Technology)
Electric vehicles (EVs) provide a primary alternative for mitigating greenhouse gas emissions in the transportation sector. Nonetheless, their extensive use poses concerns, including a rise in throwaway batteries, which, if inadequately managed, may result in heightened human toxicity. Therefore, the establishment of a circular supply chain (CSC) for EVs is crucial for ensuring long-term sustainability. This study seeks to investigate circularity potentials of end of life (EoL) EVs, influential factors, modeling approaches, and policy interventions that promote the implementation of a CSC for EVs based on a systematic review of empirical-based literature following the PRISMA framework. The findings highlight that, under an optimized waste hierarchy, approximately 55.1–59.5 % of EV components can be reused, 24.4−31.8 % repurposed, 55.1−59.5 % remanufactured, and 95.6−96.0 % recycled, leaving about 23.5–24.7 % of components destined for landfills. Five factors pertaining to regulations, economics, environment, technology and infrastructure, ecosystem were identified to be influential for the CSC implementation for EVs. These factors are modeled using either optimization, simulation, or hybrid approach, depending on the modeling objective and settings, in order to comprehend the CSC system, support decision-making and enhance resource recovery strategies. Policy interventions primarily focused on collection and transportation, technology and infrastructure, and economic aspects, have recently been expanded to encompass social interventions, design standardization, and stakeholder collaboration. Given the potential circularity of EV components, the multifaceted factors involving various stakeholders should be addressed in designing and implementing CSC system for a more resource-efficient future of EVs.